KONDISI KREDIT USAHA SELAMA PANDEMI DI PROVINSI JAWA BARAT - Berta Dian Theodora (Universitas Indraprasta PGRI Jakarta, 2021)
The value of credit disbursed to businesses continues to increase every year, but when a pandemic condition occurs, it is seen that the amount of business credit granted by the bank each month fluctuates. West Java Province is the province with the largest population, namely 49.94 million people, administratively the government is divided into 27 districts/cities. The aim of the research is to determine the condition of business credit in every district and city during the pandemic. The type of research data is secondary data originating from the Bank Indonesia and BPS of West Java province. Quantitative research and descriptive methods with sample data are MSMEs business credit in districts and cities in West Java from April 2020 to April 2021. The results obtained by credit to small and medium enterprises have increased but credit to micro enterprises is decreasing every month. Business credit is part of financial capital and is one of the factors that determine the amount of output, so that the addition of business credit is expected to be a factor driving economic growth and ultimately absorb labor.